2020
DOI: 10.1089/hum.2019.287
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous miR-29a Attenuates Muscle Atrophy and Kidney Fibrosis in Unilateral Ureteral Obstruction Mice

Abstract: Renal fibrosis leads to end-stage renal disease, but antifibrotic drugs are difficult to develop. Chronic kidney disease often results in muscle wasting, and thereby increases morbidity and mortality. In this work, adeno-associated virus (AAV)mediated overexpressing miR-29a was hypothesized to counteract renal fibrosis and muscle wasting through muscle-kidney crosstalk in unilateral ureteral obstruction (UUO) mice. miR-29a level was downregulated in the kidney and skeletal muscle of UUO mice. The secretion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
(53 reference statements)
1
21
0
Order By: Relevance
“…A disintegrin and metalloproteinases (ADAMs) are involved in renal fibrosis and TGF‐β/Smad2/3 signaling upregulates Adam 10, 12, 17, 19 expression in renal cells and in unilateral ureteral obstruction models of renal fibrosis 35 . The increase in Adams12 and 19 expression correlated strongly with a decrease in miR‐29s expression and the overexpression of miR‐29s blocked TGF‐β‐mediated upregulation of Adam12 and Adam19 gene expression and improve renal fibrosis 35,36,176 . These studies strongly suggest ADAMs are involved in renal fibrosis and are regulated by both miR‐29s and TGF‐β making thempotential therapeutic targets for the prevention of renal fibrosis.…”
Section: Role Of Mir‐29 Family In Cardiorenal Syndromementioning
confidence: 92%
“…A disintegrin and metalloproteinases (ADAMs) are involved in renal fibrosis and TGF‐β/Smad2/3 signaling upregulates Adam 10, 12, 17, 19 expression in renal cells and in unilateral ureteral obstruction models of renal fibrosis 35 . The increase in Adams12 and 19 expression correlated strongly with a decrease in miR‐29s expression and the overexpression of miR‐29s blocked TGF‐β‐mediated upregulation of Adam12 and Adam19 gene expression and improve renal fibrosis 35,36,176 . These studies strongly suggest ADAMs are involved in renal fibrosis and are regulated by both miR‐29s and TGF‐β making thempotential therapeutic targets for the prevention of renal fibrosis.…”
Section: Role Of Mir‐29 Family In Cardiorenal Syndromementioning
confidence: 92%
“…Several lines of evidence suggest that miR-29a is an important antifibrotic agent in the kidney. Expression of miR-29a was reduced in the kidney in rodent UUO models [ 149 ] and in urinary exosomes from CKD patients [ 150 , 151 , 152 ], while renal fibrosis was suppressed after administration of AAV-miR-29 in mice with UUO or DN [ 153 ]. Muscle satellite cell exosomes engineered to contain enriched levels of miR-29a and to elaborate a surface RVG-moiety that targeted acetylcholine receptors in the kidney were therapeutic after intramuscular injection in the UUO model [ 154 ].…”
Section: Renal Fibrosismentioning
confidence: 99%
“…Levels of vitronectin in urine and urinary EVs [ 161 ] or of miR-21 in plasma EVs [ 162 ] were proposed as biomarkers for post-kidney transplantation patients with a high incidence of tubulointerstitial fibrosis. Finally, miR-29a was elevated in serum EVs from mice with UUO [ 153 ] and plasma-derived exosomal miRs in rats that had undergone 5/6th partial nephrectomy or two-kidney-one-clip were associated with pathways of fibrosis and injury and could be discriminated from free plasma miRs [ 163 ].…”
Section: Renal Fibrosismentioning
confidence: 99%
“…miR-29 expression was downregulated following myocardial infarction and after treatment of isolated heart fibroblasts with TGF-β [ 112 ]. Overexpression of miR-29 inhibited the pro-fibrotic response in isolated cardiac fibroblasts and in animal models [ 113 , 114 ]. These studies focused on endogenous miR-29 in cardiac fibroblasts; however, recent studies have shown that miR-29 carried by exosomes is able to reduce skeletal muscle atrophy and kidney fibrosis in a unilateral ureteral obstruction-induced model of kidney disease [ 114 ].…”
Section: Role Of Exosomes In Fibrosis and Fibroblast Activationmentioning
confidence: 99%